The effects of administration of melatonin in uterine torsion - Risvanli, A.; Saat, N.; Dogan, H.; Sahna, E. (Wiley-Blackwell, 2016)
[Abstract Not Available]
Joint Meeting of the 20th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) / 13th Conference of the Spanish-Association-for-Animal-Reproduction (AERA) -- OCT 27-29, 2016 -- Lisbon, PORTUGAL